Pengaruh Model Pembelajaran Somatic, Auditory, Visualization, Intellectual (SAVI) Terhadap Hasil Belajar Peserta Didik pada Materi Bumi dan Tata Surya - Zulhanif, Halimatun Saqdiah; Lestari, Tuti; Yurnetti, Yurnetti; Wati, Fatma (Indo-MathEdu Intellectuals Journal, 2025)
This study is conducted against the backdrop of low student learning outcomes in science classes and the widespread use of teacher-centered learning approaches. This research aims to determine the effect of applyig the SAVI (Somatic, Auditory, Visualization, Intellectual) model on the learning outcomes of class VII students SMPN 1 Batusangkar. This research population includes all class VII students of SMPN 1 Batusangkar, and pusposive sampling was used to determine the sampel in the study. The instruments used in study are test instrumen in the form of multiple-choice questions and non-test instruments in the form of observation sheets. The generated data is analyzed quantitatively in a descriptive manner. According to the data analysis results, Ha was accepted and H0 was refused, The rejection of H0 was supported by the t-n-gain test, which show a t-count value of 3.17 ≥ t-table value of 1.99. This suggests that the learning outcomes of the two samples differ significantly, indicating that the SAVI model's application influences students' learning outcomes, especially when it comes to Earth and the solar system.